The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2135/cropsci2016.02.0123
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Iron Sulfate Affect Microdochium Patch Severity and Turf Quality on Annual Bluegrass Putting Greens

Abstract: Microdochium patch is an important turfgrass disease in cool‐humid regions and is caused by the pathogen Microdochium nivale (Fries) Samuels & Hallett. Control of the pathogen is necessary to provide acceptable putting‐green‐quality turf, and fungicide applications are the predominant method of control. Increasing pesticide restrictions have generated interest in alternative management techniques of Microdochium patch. This research evaluated the effects of three nitrogen and five iron sulfate rates on Microdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 11 publications
1
25
2
Order By: Relevance
“…Iron sulfate applications are known to decrease soil pH (Carrow, Waddington, & Rieke, 2001), and pH has been demonstrated to affect the growth of Microdochium nivale (Bennett, 1933). Previous field trials have also demonstrated that acidifying products, fertilizers and sulfur fungicides can suppress Microdochium patch and lead to a lower soil pH (Brauen, Goss, Gould, & Orton, 1975;Mattox et al, 2016) or reduce the number of fungicide applications (McDonald, Mattox, Gould, & Kowalewski, 2018). With the effects of pH on T A B L E 1 Effects of 97.6 kg FeSO 4 ⋅7H 2 O ha −1 applied at different water carrier volumes and non-treated control (NTC) on turfgrass quality ratings on an annual bluegrass putting green in Corvallis, OR.…”
Section: Microdochium Patch Suppressionmentioning
confidence: 99%
“…Iron sulfate applications are known to decrease soil pH (Carrow, Waddington, & Rieke, 2001), and pH has been demonstrated to affect the growth of Microdochium nivale (Bennett, 1933). Previous field trials have also demonstrated that acidifying products, fertilizers and sulfur fungicides can suppress Microdochium patch and lead to a lower soil pH (Brauen, Goss, Gould, & Orton, 1975;Mattox et al, 2016) or reduce the number of fungicide applications (McDonald, Mattox, Gould, & Kowalewski, 2018). With the effects of pH on T A B L E 1 Effects of 97.6 kg FeSO 4 ⋅7H 2 O ha −1 applied at different water carrier volumes and non-treated control (NTC) on turfgrass quality ratings on an annual bluegrass putting green in Corvallis, OR.…”
Section: Microdochium Patch Suppressionmentioning
confidence: 99%
“…However, Ervin et al (2017) reported that overall creeping bentgrass quality was lower during the summer in plots treated with 48.8 kg ha −1 of ferrous sulfate than in plots treated with 24.4 kg ha −1 . Additionally, Mattox et al (2017) reported significant annual bluegrass quality decline associated with turfgrass thinning and foliar toxicity in plots treated with ferrous sulfate applied at 97.65 kg ha −1 . This unintentional consequence of ferrous sulfate usage for disease suppression leads researchers to explore lower use rates to negate the potential for turfgrass injury.…”
Section: Crop Sciencementioning
confidence: 99%
“…The use of ferrous sulfate as an alternative to fungicides has proven effective in turfgrass systems (Mattox et al., 2017; McCall et al., 2016). Iron applications for pathogen suppression was first noted by Forsyth (1957).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations